Penerapan Metode Role Play untuk Meningkatkan Keaktifan Belajar Pendidikan Agama Katolik di SMPN 3 Tujuh Belas - Pasifikus Pasifikus; FR Wuriningsih (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to examine the effectiveness of the role-play learning method in increasing student learning activeness in the subject of Catholic Religious Education. The background of this research is the low level of student participation and engagement during classroom learning, particularly in expressing values, responding to questions, and participating in discussions. This classroom action research was conducted in two cycles involving students of Grade VII at SMP Negeri 3 Tujuh Belas, Bengkayang. The method employed consists of planning, action, observation, and reflection in each cycle. Data were collected using observation sheets, student activity assessments, and reflection notes. The findings are expected to show that the role-play method encourages students to be more active, expressive, and participatory in learning activities. The implications of this research highlight the importance of interactive, student-centered learning models in strengthening the internalization of religious values and improving learning dynamics in the classroom.